Implications of field relations and U-Pb geochronology for the age of gold mineralization and timing of Acadian deformation in northern New Brunswick - McCutcheon, Steven; Bevier, Mary (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1990)
In the Upsalquitch Forks area (NTS 21 O/10), penetratively deformed sedimentary and volcanic rocks of the Silurian Chaleurs Group and Lower Devonian Dalhousie and Tobique groups were intruded by abundant syn- to post-tectonic dykes and plugs. The Mulligan Gulch porphyry, a hypabyssal felsic intrusion (with an extrusive component ?) emplaced in Upper Silurian sedimentary rocks, has yielded a U-Pb zircon age of 419 ± 1 Ma, whereas the Jerry Ferguson porphyry, a felsic intrusion that intruded Lower Devonian volcanic rocks, has yielded a U-Pb zircon age of 401 ± 1 Ma. The above ages, combined with field relationships, permit the following conclusions: (1) felsic and mafic intrusions in the Upsalquitch Forks area are more or less coeval with volcanic rocks of the Chaleurs, Dalhousie and Tobique groups; (2) most gold occurrences in the area are genetically related to mafic intrusions and, therefore, formed in Late Silurian to Early Devonian time; (3) penetrative deformation in the area was predominantly a Silurian rather than a Devonian process and therefore was not Acadian sensu stricto; (4) Late Silurian to Early Devonian igneous activity occurred in a compressive, rather than an extensional, tectonic setting.